2019
DOI: 10.1021/acsnano.9b05908
|View full text |Cite
|
Sign up to set email alerts
|

A Class of Catalysts of BiOX (X = Cl, Br, I) for Anchoring Polysulfides and Accelerating Redox Reaction in Lithium Sulfur Batteries

Abstract: The lithium–sulfur battery system contains a complex reaction process of sulfur involving multielectron reactions and phase conversions. Moreover, the diffusion of intermediate polysulfides during reduction and sluggish kinetic conversion of polysulfides into insoluble Li2S still plague the use of Li–S batteries. Herein, BiOX was employed as sulfur host material in Li–S batteries, which could integrate suppression of the shuttle effect and promote kinetics redox reactions of lithium polysulfides. The polar BiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 33 publications
4
67
1
Order By: Relevance
“…Extensive efforts have been devoted to constructing the cathode of lithium–sulfur (Li–S) batteries to meet the ever‐increasing energy demands due to the abundant reserves of the materials involved, and affordable cost. [ 1–3 ] However, the commercial application of the sulfur cathode for the Li–S batteries is restrained by several technical barriers [ 4–6 ] compared with Li‐ion battery. [ 7 ] First, the poor conductivity of sulfur and its reaction intermediates limit the sulfur utilization, [ 8 ] which leads to decreased energy density and power density.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive efforts have been devoted to constructing the cathode of lithium–sulfur (Li–S) batteries to meet the ever‐increasing energy demands due to the abundant reserves of the materials involved, and affordable cost. [ 1–3 ] However, the commercial application of the sulfur cathode for the Li–S batteries is restrained by several technical barriers [ 4–6 ] compared with Li‐ion battery. [ 7 ] First, the poor conductivity of sulfur and its reaction intermediates limit the sulfur utilization, [ 8 ] which leads to decreased energy density and power density.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial to separate these signals from each other, with the purpose of the improvement of selectivity and sensitivity of DA determination [14][15][16][17]. To solve this problem, different modified electrodes based on the carbon nanomaterials, metal nanoparticles, composites, polymers, and metal oxides have been provided to determine the dopamine [18][19][20]. Recently some nanocomposites containing metal oxides such as CuTRZMoO 4 @PPyÀ n [21], Co 3 O 4 /GO [22], AuÀ ZnO NCAs [23] and TiO 2 À WO 3 [24] have been used for electrochemical determination of DA .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, the issues related to dissolution of polysulfide during charge and discharge are the main obstacles to the commercialization of LiÀ S batteries. [6][7][8][9] To solve these problems, many groups have focused on the application of porous carbons for LiÀ S batteries. Ever since Ji et al [10] demonstrated the potential of S/CMK-3 (obtained by the melt-diffusion method) for high-capacity applications, many researchers have focused on the fabrication of S/C composites.…”
Section: Enhancing the Of Performance Of Lithium-sulfur Batteries Thrmentioning
confidence: 99%